2017
DOI: 10.1093/mnras/stx1596
|View full text |Cite
|
Sign up to set email alerts
|

Physical drivers of galaxies’ cold-gas content: exploring environmental and evolutionary effects with Dark Sage

Abstract: We combine the latest spectrally stacked data of 21-cm emission from the ALFALFA survey with an updated version of the Dark Sage semi-analytic model to investigate the relative contributions of secular and environmental astrophysical processes on shaping the H i fractions and quiescence of galaxies in the local Universe. We calibrate the model to match the observed mean H i fraction of all galaxies as a function of stellar mass. Without consideration of stellar feedback, disc instabilities, and active galactic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 131 publications
(204 reference statements)
4
68
0
4
Order By: Relevance
“…The main cause of disturbances in galaxy groups are tidal interactions, and it is still an open question whether rampressure stripping occurs in groups (Westmeier et al 2011;Rasmussen et al 2012;Brown et al 2016;Stevens & Brown 2017). Studying individual galaxies in large loose groups, Kilborn et al (2009) found that the H i deficient galaxies are likely to be within a projected distance of 1 Mpc from the group centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main cause of disturbances in galaxy groups are tidal interactions, and it is still an open question whether rampressure stripping occurs in groups (Westmeier et al 2011;Rasmussen et al 2012;Brown et al 2016;Stevens & Brown 2017). Studying individual galaxies in large loose groups, Kilborn et al (2009) found that the H i deficient galaxies are likely to be within a projected distance of 1 Mpc from the group centre.…”
Section: Discussionmentioning
confidence: 99%
“…Referring back to hierarchical structure formation theory, a galaxy embedded in the centre of a dark matter halo (central galaxy) grows as it accretes satellite galaxies, over time becoming the most massive and the brightest galaxy (White & Rees 1978;Brough et al 2006). In this scenario, the satellite galaxies are moving with respect to the centre of group potential and experiencing environmental effects, thus in theory they are going through a different evolutionary path from that of the central galaxy (White & Rees 1978;Yang et al 2007;Brown et al 2017;White & Rees 1978;Brough et al 2006;Stevens & Brown 2017). Observationally, and in simulations, it is often difficult to distinguish between the central and satellite galaxy, especially in a small groups (Berlind et al 2006;Campbell et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our asymmetric galaxies are therefore tracing a population where Hi is being disturbed and removed. One interpretation of this is that environmental processes, such as ram pressure or tidal stripping (Gunn & Gott 1972;Kenney et al 2004;Stevens & Brown 2017), might be the dominant driver of Hi asymmetries in xGASS. Quantitatively 25% and 15% of the matched asymmetric and symmetric samples (respectively) are satellites, indicating a stronger contribution of galaxies potentially undergoing environmental effects to the asymmetric sample.…”
Section: Hi Properties Of the Asymmetric Populationmentioning
confidence: 99%
“…Atomic hydrogen (Hi) has proven to be a powerful tracer of these gas reservoirs though its 21cm emission line. It is typically detectable to 2-3 times the radius of the optically bright stellar component of galaxies (Giovanelli & Haynes 1988;Wang et al 2014) where baryons are less gravitationally bound and more sensitive to galaxy interactions and environmental processes (Gunn & Gott 1972;Kenney et al 2004;Stevens & Brown 2017). While to date there exists ∼ 500 spatially resolved observations of the Hi in galaxies in the local Universe (Wang et al 2016) the majority of the data are unresolved, in the form of the spatially integrated global Hi spectrum produced by blind surveys such as the Arecibo Legacy Fast ALFA survey (ALFALFA, Giovanelli et al 2005;Haynes et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to adopting this low-metallicity floor would be to simply allow for the initial enrichment to happen from other channels of star formation, e.g. instabilities and mergers (Stevens & Brown 2017).…”
Section: H 2 Formationmentioning
confidence: 99%